Japanese short stories for beginners : 20 captivating short stories to learn Japanese & grow your vocabulary the fun way!. (Easy Japanese stories., 2020)
" ... In this book we have compiled 20 easy-to-read, compelling and fun stories that will allow you to expand your vocabulary and give you the tools to improve your grasp of the wonderful Japanese language."--Back cover